Implementation of the Human Development Index Improvement Program in North Kalimantan Province - Mochammad Sarkawi; Muh. Akmal Ibrahim; Badu Ahmad; Sawedi Muhammad; Didik Iskandar (Journal of Public Representative and Society Provision, 2024)
This study aims to analyze the effectiveness of human development policy implementation in North Kalimantan Province using Merilee S. Grindle's (1980) implementation model, which emphasizes two main aspects, namely policy content and implementation context. This study uses a qualitative approach involving various stakeholders involved in the implementation of the Human Development Index (HDI) improvement program. The results show that human development policies in North Kalimantan have become a top priority for the local government, Regional Medium-Term Development Plan (RPJMD) and supported by regional regulations in the fields of education and health. The implementation of this policy shows positive progress with an increase in the HDI from 71.01 in 2020 to 72.10 in 2024. However, its effectiveness is not yet optimal because it still faces various obstacles such as limited human resources, weak cross-sectoral coordination, interregional disparities, and unequal access to basic services in rural and border areas. Analysis based on the Grindle model shows that the success of the policy is greatly influenced by the ability of local governments to adaptively manage social, economic, and institutional dynamics. Thus, strengthening bureaucratic capacity, inter-agency synergy, and equitable access to education, health, and economic services are important steps to accelerate the improvement of human development quality in North Kalimantan Province.